2017
DOI: 10.4172/2155-9538.1000217
|View full text |Cite
|
Sign up to set email alerts
|

Study on Pulsed Electromagnetic Fields Regulate the mRNA Expression of V-ATPase, CAII, NFAT2 and RANK in an Ovariectomized Rat Model of Osteoporosis Mechanism Analysis

Abstract: We investigated the mRNA expression of V-ATPase CA II, NFAT2, and RANK as well as bone mineral density (BMD) in bilaterally ovariectomized (OVX) rats treated with pulsed electromagnetic fields (PEMF), to explore the mechanism by which PEMF alter bone at the molecular level in vivo. 24 Sprague-Dawley female rats were randomly divided into three different groups: SHAM, OVX, ovariectomy with PEMF stimulation (PEMF+OVX). The PEMF frequency was 3.8 mT, 8 Hz, for 40 min per day. Eight rats in each group were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Bassey et al [1], developed a mathematical model for scoring the optimal benefits of chemotherapy with respect to the patients' CD4+ T-cell counts in response to Reverse Transcriptase Inhibitor (RTI) treatment. Huang et al [2], postulated that, the positive effects of Pulsed Electromagnetic Fields (PEMF) on bone structure can be attributed to its regulation of bone resorption, and elevation of the Bone Mineral Density (BMD), through the intervention of the RANK and CN/NFAT pathways. Xiaobing Yu et al [3], found that FERA, IERA and VERA can be used as a diagnostic reference for Anterior Cruciate Ligament (ACL) injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bassey et al [1], developed a mathematical model for scoring the optimal benefits of chemotherapy with respect to the patients' CD4+ T-cell counts in response to Reverse Transcriptase Inhibitor (RTI) treatment. Huang et al [2], postulated that, the positive effects of Pulsed Electromagnetic Fields (PEMF) on bone structure can be attributed to its regulation of bone resorption, and elevation of the Bone Mineral Density (BMD), through the intervention of the RANK and CN/NFAT pathways. Xiaobing Yu et al [3], found that FERA, IERA and VERA can be used as a diagnostic reference for Anterior Cruciate Ligament (ACL) injury.…”
mentioning
confidence: 99%
“…Low frequency, single pulse electromagnetic fields have been observed to suppress trabecular bone loss and restore trabecular bone structure and in rat models of osteoporosis. Huang et al [2], investigated the transcript levels of biomolecules in involved in osteogenesis and bone resorption to account for the beneficial effects mediated by PEMF. Towards this, the authors analysed the expression of CAII, NFAT2, RANK, and VATPase transcripts in rat models of osteoporosis.…”
mentioning
confidence: 99%